Land conversion transforming urban military baselands to higher economic uses - Mundo, Proscoro Ervin A. (2014)
Access online through this link: https://journals.upd.edu.ph/index.php/SURP/article/view/4192/3798
Keywords: Public-private sector cooperation; Economic development; Military camps; Armed Forces of the Philippines